Indonesian Vocational High School Readiness Toward Society 5.0 - Wibawanto, Hilmawan; Roemintoyo, Roemintoyo; Rejekiningsih, Triana (Journal of Education Reseach and Evaluation, 2021)
Vocational high school comprehensively relates technology studies, the development of acquisition of practical skills, attitudes, and life skills. In this context, teachers play important role in forming and producing competent graduates’ need toward Society 5.0. This study aims to analyze teachers’ perceptions about vocational high school readiness toward Society 5.0. This study used a descriptive quantitative with survey method. The respondents were vocational high school teachers that have been selected using a random sampling method. The result indicated teachers’ understanding of Society 5.0 is low. The school’s readiness to facilitate learning also quite low. The assessments still generalized requirements for student achievement. On the other hand, teachers still have the motivation to learn to use technology. The majority of teachers often attend training to improve instructional media skills. Based on these results, school preparation needs to be improved in terms of teacher competence and learning support facilities for Society 5.0.